Protective Effect and Possible Mechanisms of Astragaloside IV in Animal Models of Diabetic Nephropathy: A Preclinical Systematic Review and Meta-Analysis - Wang, Hong; Zhuang, Zhuang; Huang, Yue-Yue; Zhuang, Zhi-Zhi; Jin, Yi; Ye, Han-Yang; Lin, Xiao-Ji; Zheng, Qun; Wang, Yi-Luan (Frontiers in Pharmacology, 2020)
Astragaloside IV (AS-IV) has a variety of biological activities and is widely used to treat kidney diseases. We conducted a systematic review of 24 animal studies including 424 animals to evaluate the efficacy of AS-IV for diabetic nephropathy (DN); all current possible mechanisms were summarized. A search strategy was applied to eight databases from inception to June 2020. The CAMARADES 10-item quality checklist and Rev-Man 5.3 software were used to analyze the risks of bias of each study and data regarding outcome measures, respectively. The mean study quality score was 5.4 points (range 3–8 points). Meta-analyses data and comparisons between groups showed that AS-IV significantly slowed the progression of pathological signs in the kidney including glomeruli and tubules, increasing creatinine clearance rate, decreasing blood urea nitrogen, serum creatinine, 24-hour urinary neutrophil gelatinase-associated lipocalin and N-acetyl-β-D-glucosaminidase, 24-hour urinary albumin, 24-hour urinary microalbumin and HbA1c. There were no significant differences between experimental and control groups with respect to mortality or levels of alanine aminotransferase and aspartate aminotransferase. In terms of the possible mechanisms of treatment of DN, AS-IV acts through anti-fibrotic, antioxidant, and anti-apoptotic mechanisms, thereby alleviating endoplasmic reticulum stress, inhibiting mitochondrial fission and increasing autophagic activity. Taken together, our findings suggest that AS-IV is a multi-faceted renoprotective candidate drug for DN.